The Intervention of Philology Gender, Learning, and Power in Lohenstein's Roman Plays - Newman, Jane O. (UNC Studies in the Germanic Languages and Literatures, 2000)
This book examines the interplay of history, textuality, dramaturgy, and politics in the school dramas of Daniel Casper von Lohenstein (1635-1683). The plays are based on well-known episodes from classical Roman history and were staged in Breslau by students at two all-male humanistic gymnasia. Organized exclusively around stories of such female protagonists as Agrippina, Cleopatra, Epicharis, and Sophonisbe, these productions required that the young actors dress as women to play roles that routinely involved scenes of political intrigue, incest, seduction, torture, and threatened infanticide. In print these plays were accompanied by massive annotational apparatuses that delineate the contours of the learned universe of eastern central Europe in exacting detail. Newman's study sheds light on the ideological complexity of gender, politics, and learned culture in the early modern period as it emerges from these intriguing and often bizarre plays.